Acid Exposure Induces Multiplication of Salmonella enterica Serovar Typhi - Ahirwar, Suneel Kumar (J Clin Microbiol, 2014)
Salmonella enterica serovar Typhi faces several environmental stresses while going through the stomach (acidic pH) to the small intestine (basic pH) and intracellularly in macrophages (acidic pH) in humans. The acidic pH followed by alkaline pH in the small intestine might be responsible for expression of certain stress-induced genes, resulting in not only better survival but also induction of multiplication and invasion of the bacterium in the small intestine. Based on this hypothesis, we developed a process wherein we exposed the blood, urine, and stool specimens from 90 acute typhoid fever patients and 36 chronic typhoid carriers to acidic pH to see the effect on isolation rate of S. Typhi. About 5 g of freshly passed unpreserved stool, a centrifuged deposit of 15 ml of urine, and 5 ml of blood clot were subjected to 5 ml of Luria-Bertani (LB) broth (pH 3.5) for 20 min, followed by enrichment in bile broth-selenite F broth. When the combined isolation from all 3 specimens, i.e., blood, urine, and stool, after acid exposure was considered, a total of 77.7% of the acute typhoid patients were observed to be positive for the isolation of the S. Typhi serotype, compared to 8.8% by the conventional method. Similarly, 42% (15/36) of chronic carriers yielded positive for S. Typhi growth after acid exposure, compared to 5.5% (2/36) by the conventional method. It therefore can be concluded that acid shock triggers the multiplication of the bacteria, resulting in better isolation rates from blood clot, stool, and urine specimens.